Evolution of 𝜷-Cell Replacement Therapy in Diabetes Mellitus: Islet Cell Transplantation - Cyrus Jahansouz; Cameron Jahansouz; Sean C. Kumer; Kenneth L. Brayman (Journal of Transplantation)
Diabetes mellitus remains one of the leading causes of morbidity and mortality worldwide. According to the Centers for Disease Control and Prevention, approximately 23.6 million people in the United States are affected. Of these individuals, 5 to 10% have been diagnosed with Type 1 diabetes mellitus (T1DM), an autoimmune disease. Although it often appears in childhood, T1DM may manifest at any age, leading to significant morbidity and decreased quality of life. Since the 1960s, the surgical treatment for diabetes mellitus has evolved to become a viable alternative to insulin administration, beginning with pancreatic transplantation. While islet cell transplantation has emerged as another potential alternative, its role in the treatment of T1DM remains to be solidified as research continues to establish it as a truly viable alternative for achieving insulin independence. In this paper, the historical evolution, procurement, current status, benefits, risks, and ongoing research of islet cell transplantation are explored.